Increased Levels of IFN-γ, PAI-1, and NT-proBNP are Associated with the Occurrence of Hypoxemia in COVID-19 - Fathur Nur Kholis; Nur Farhanah; Charles Limantoro; Nyoman Suci Widyastiti; Mochamad Ali Sobirin (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Acute respiratory distress syndrome (ARDS) is one of the severe complications of Coronavirus disease 2019 (COVID-19) that can lead to the occurrence of hypoxemia. Hypoxemia occurs due to the role of pro-inflammatory cytokines and coagulation factors. Several studies have shown that interferon (IFN)-γ, plasminogen activator inhibitor 1 (PAI-1) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) are biological markers that can be used to evaluate the severity and prognosis of the disease in severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection. This study was conducted to evaluate the association between IFN-γ, PAI-1, NT-proBNP and hypoxemia in COVID-19 patients.METHODS: This was a cross-sectional study of COVID-19 subjects with hypoxemia. Hypoxemia assessment was performed based on arterial blood gas analysis. IFN-γ and PAI-1 were measured with ELISA, while NT-proBNP levels were measured with Roche NT-proBNP.RESULTS: Fifty-five COVID-19 subjects with hypoxemia were observed. Thirty subjects experiencing moderate to severe hypoxemia and 25 with mild hypoxemia. Levels of IFN-γ, PAI-1, and NT-proBNP were higher in COVID-19 subjects with moderate to severe hypoxemia compared to those with mild hypoxemia (261.14 (121-348.60) pg/mL vs. 145.50 (59.90-348.60) pg/mL, p<0.001; 5.47 (3.50-8.50) pg/mL vs. 3.40 (2.20-9.30) pg/mL, p<0.001; 760 (112-34,066) pg/mL vs. 71 (48-364) pg/mL, p<0.001).CONCLUSION: Elevated levels of IFN-γ, PAI-1, and NT-proBNP are associated with hypoxemia in COVID-19 patients, suggesting that these markers may be useful in assessing hypoxemia in COVID-19 patients.KEYWORDS: IFN-γ, PAI-1, NT-proBNP, hypoxemia, COVID-19